PENGARUH TEORI KOGNITIF SOSIAL BANDURA MELALUI MEDIA KOMIK EDUKASI TERHADAP KEPATUHAN TATA TERTIB SEKOLAH - Vinda Permatasari; Wahyu Nugroho; Intan Susetyo Kusumo Wardhani (LPPM STAI Muhammadiyah Probolinggo, 2026)
Student compliance with school rules is an important part of character building, especially in developing discipline and responsibility. However, some students still do not fully follow school rules, so innovative learning methods are needed to encourage positive behavior through engaging learning experiences. This study aims to examine the effect of Bandura’s Social Cognitive Theory implemented through educational comics on student compliance with school rules. This research adopted a quantitative quasi-experimental method using a non-equivalent control group design. The participants included 39 fifth-grade students, who were divided into an experimental group of 20 students and a control group of 19 students. A questionnaire was administered both before and after the intervention to obtain the research data. Subsequently, the collected data were examined through normality and homogeneity tests, followed by an Independent Samples t-test using SPSS version 25. The experimental group demonstrated a greater improvement, with a score increase of 5.45 points, whereas the control group recorded an increase of 1.48 points. Based on the hypothesis testing results, the Independent Samples t-test revealed a t-value of 2.183 and a p-value of 0.035, which was below the 0.05 significance threshold, indicating that educational comics based on Bandura’s Social Cognitive Theory affect student compliance. Integrating educational comics into Pancasila Education offers an alternative instructional strategy that helps promote students' character development